2021
DOI: 10.3389/fmolb.2021.670815
|View full text |Cite
|
Sign up to set email alerts
|

Potent Molecular Feature-based Neutralizing Monoclonal Antibodies as Promising Therapeutics Against SARS-CoV-2 Infection

Abstract: The 2019–2020 winter was marked by the emergence of a new coronavirus (SARS-CoV-2) related disease (COVID-19), which started in Wuhan, China. Its high human-to-human transmission ability led to a worldwide spread within few weeks and has caused substantial human loss. Mechanical antiviral control approach, drug repositioning, and use of COVID-19 convalescent plasmas (CPs) were the first line strategies utilized to mitigate the viral spread, yet insufficient. The urgent need to contain this deadly pandemic has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 162 publications
(280 reference statements)
2
24
0
Order By: Relevance
“…Both of these bispecific antibodies exhibited higher therapeutic efficacy than the equivalent cocktail of CoV-14 and CoV-06 antibodies [ 244 ], indicating the potential power of combining antibodies into a single molecule over using cocktails of multiple antibodies [ 331 ]. As might be expected from previous work [ 321 ], the tetravalent IgG-(scFv) 2 bispecific antibody comprised of CoV-14 and CoV-06 was superior to the CrossMAb format as well as the two-antibody cocktail in SARS-CoV-2 neutralization activity in vitro, including broad neutralization of escape variants, and enhanced protective efficacy in vivo [ 331 ]. This is one example of the principle, described throughout this work, that an increase in antibody valency correlates with an increased ability to neutralize SARS-CoV-2 [ 332 , 333 ].…”
Section: Anti-sars-cov-2 Igg Antibodiesmentioning
confidence: 53%
See 1 more Smart Citation
“…Both of these bispecific antibodies exhibited higher therapeutic efficacy than the equivalent cocktail of CoV-14 and CoV-06 antibodies [ 244 ], indicating the potential power of combining antibodies into a single molecule over using cocktails of multiple antibodies [ 331 ]. As might be expected from previous work [ 321 ], the tetravalent IgG-(scFv) 2 bispecific antibody comprised of CoV-14 and CoV-06 was superior to the CrossMAb format as well as the two-antibody cocktail in SARS-CoV-2 neutralization activity in vitro, including broad neutralization of escape variants, and enhanced protective efficacy in vivo [ 331 ]. This is one example of the principle, described throughout this work, that an increase in antibody valency correlates with an increased ability to neutralize SARS-CoV-2 [ 332 , 333 ].…”
Section: Anti-sars-cov-2 Igg Antibodiesmentioning
confidence: 53%
“…Although hundreds of potent nAbs have been successfully isolated (cf., [ 290 , 321 ]), studies on antibody resistance have demonstrated that rapid viral escape arises with any monotherapy regardless of antibody neutralizing activity and epitope conservation [ 322 324 ]. Thus, many researchers and companies have turned to a rational combination of at least two neutralizing antibodies that possess different, non-overlapping epitopes together as a combination therapeutic to provide broader epitope coverage, and hopefully, greater resistance against variants that may arise over time [ 211 , 245 , 261 , 325 ].…”
Section: Anti-sars-cov-2 Igg Antibodiesmentioning
confidence: 99%
“…SARS-CoV-2 neutralizing antibodies are derived from COVID-19 convalescent patients, phage display, naïve libraries, or other strategies [ 20 ]. The neutralizing antibodies can be classified into three sets targeting the receptor-binding domain (RBD), the N-terminal domain (NTD), or S2 subunit of SARS-CoV-2 spike (S) glycoprotein [ 20 , 21 ] ( Figure 2 A). RBD-directed neutralizing antibodies can be further divided into six groups (group A-F) [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spike mutation at residue K417 in almost all VOCs, but not the Alpha variant, has been predicted to cause an overwhelmingly disruptive effect, which may make these variants resistant to vaccine-induced humoral immunity ( 3 , 12 ). Overall, at the molecular level, these spike mutations induce molecular tridimensional changes at the antibody binding sites, which become inaccessible for antibodies and therefore impede antibody binding ( 20 , 21 ). Also, the residues changed are such that mutations induce an increased binding affinity (or interaction force) of RBD to angiotensin-converting enzyme 2 (ACE2), like in the cases of mutations V367F, L452Q, N501Y, and D614G, which is associated with increased transmissibility ( 1 , 10 , 11 , 21 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, at the molecular level, these spike mutations induce molecular tridimensional changes at the antibody binding sites, which become inaccessible for antibodies and therefore impede antibody binding ( 20 , 21 ). Also, the residues changed are such that mutations induce an increased binding affinity (or interaction force) of RBD to angiotensin-converting enzyme 2 (ACE2), like in the cases of mutations V367F, L452Q, N501Y, and D614G, which is associated with increased transmissibility ( 1 , 10 , 11 , 21 23 ).…”
Section: Introductionmentioning
confidence: 99%